Internalisasi Nilai Aswaja An-Nahdliyyah dalam Kerangka Islam Nusantara dan Implementasinya pada Pendidikan Agama Islam - aminulloh nawawi (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2026)
This study aims to examine the values of Ahlussunnah wal Jama'ah (Aswaja) An-Nahdliyyah from the perspective of Islam Nusantara and to analyze their implementation in Islamic Religious Education (Pendidikan Agama Islam/PAI) as an effort to strengthen religious moderation in Indonesia. The study is motivated by the growing challenges of intolerance, radicalism, and the declining attitude of mutual respect within Indonesia's pluralistic society, highlighting the need to reinforce moderate Islamic values through education. This research employs a qualitative approach using the library research method. Data were analyzed descriptively and analytically through an extensive review of scholarly literature, classical Islamic texts, and relevant documents. This approach provides a comprehensive understanding of the concepts of Aswaja An-Nahdliyyah and their relevance to the development of Islamic education that promotes moderate character formation. The findings indicate that the fundamental values of Aswaja An-Nahdliyyah, namely tawassuth (moderation), tawazun (balance), i'tidal (justice), tasamuh (tolerance), and ta'awun (mutual cooperation), constitute an integrated value system that shapes Muslims into moderate, inclusive, adaptive individuals who are committed to the common good. These values also reflect the distinctive character of Islam Nusantara, which accommodates local wisdom while remaining faithful to the essential principles of Islam, thereby maintaining its relevance in responding to Indonesia's socio-cultural dynamics. Furthermore, the implementation of Aswaja values in Islamic Religious Education contributes significantly to fostering tolerance, respecting diversity, strengthening social cohesion, cultivating students' moral character, and serving as a preventive strategy against the spread of radicalism and intolerance in educational institutions and society. Therefore, integrating Aswaja values into PAI learning represents a strategic approach to reinforcing religious moderation, promoting harmonious social life, and realizing a peaceful, inclusive Indonesian society grounded in both Islamic and national values.